ANALISIS BIAYA OPERASIONAL KENDARAAN (BOK) BUS RAPID TRANSIT (STUDI KASUS: TRAYEK RAJABASA – PANJANG) - Zenia F - Saraswati; Dabi Sefianiz (Universitas Negeri Padang, 2020)
As the city growing bigger in line with population, urban economics will be alongside daily transportation. The high number of daily transportation need to be accommodated with urban public transport services. In 2011, Bandar Lampung City Government provide Bus Rapid Transit (BRT) as a mass public transportation service in Bandar Lampung City. But, after about 9 (nine) years, the number of Bus Rapid Transit (BRT) route services is drop. The sustainability is questioned due to the number of passengers and operating routes continuously down, starting from 7 (seven), to 3 (three) then today is only 1 (one) left. But the city without public transportation service certainly become a bad precedent. Rajabasa Route-Panjang is the only Bus Rapid Transit (BRT) service exist. The vehicle operating costs calculation shows about IDR 648,101,870 / year, IDR 1,874,252 / day, IDR 312,375 / trip, IDR 8,255 / km, IDR 156,188 / hour and IDR 3, IDR 124 / seat needs to be provided by the regulator/government to ensure the service.